Isolation and Anti-Yeast Activity of Secondary Metabolites of Soursop Leaf Endophytic Fungi - Akhmad Endang Zainal Hasan; Dimas Andrianto; Husnawati; Faisal Rahman; Nurliani Bermawie; Heddy Julistiono; Eny Ida Riyanti (Universitas Djuanda, 2022)
This study aimed to isolate the endophytic fungi of soursop leaves that have the potential as anti-yeast. Soursop leaves were collected from 3 locations in West Java, Indonesia. The secondary metabolites produced by the endophytic fungi were extracted with ethyl acetate and tested for anti-yeast activity against Saccharomyces cerevisiae and Candida tropicalis. Profile of extracts contents characterization was carried out by using thin-layer chromatography (TLC). Twelve monoculture soursop leaves endophytic fungi isolates from Sukabumi (3 isolates), Cianjur (3 isolates), and Garut (6 isolates). It showed different abilities to inhibit C. tropicalis and S. cereviseae. The best extract is isolat from Cianjur (Sir-C1) and Sukabumi (Sir-S1). The stain patterns seen between the nine endophytic fungi extracts were similar. This indicates that the compounds in them may also be the same. But the extracts have a different absorbance for anti-yeast activities. This indicates that the total metabolites of each isolate are different. TLC results showed that ethyl acetate extraction produced almost the same metabolite components from nine endophytic fungi extracts, and all extracts had an anti-yeast activity with various absorbance. There are differences in the ability of 12 soursop leaf endophytic fungi to inhibit yeast model C. tropicalis and S. cerevisiae. Some extracts have similar TLC profiles, but their anti-yeast activity is not similar